Being Wagner the triumph of the will - Callow, Simon 1949- (William Collins, 2018)
Over a century after his death, Richard Wagner’s music dramas stand at the centre of the culture of classical music. He was a walking contradiction: aggressive, flirtatious, disciplined, capricious, heroic, visionary and poisonously anti-Semitic. His ten great mature masterpieces constitute an unmatched body of work, created against a backdrop of poverty, revolution, violent controversy, critical contempt and hysterical hero-worship. In this book, Simon Callow plunges the reader headlong into Wagner’s world, examining the intellectual and artistic climate of this composer like no other who ever lived, creator of perhaps the most sublime and most troubling body of work in the history of music. (Klappentext)
Keywords: Wagner, Richard -- 1813-1883; Deutschland; Wagner, Richard / 1813-1883; Composers / Germany / Biography; Biografie